ANALISIS USAHATANI DAN KERAGAAN MARJIN PEMASARAN JERUK DI KABUPATEN KARO - NURASA, TJETJEP; HIDAYAT, DERI (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Marketing institute is one of the important factor in horticulture agribusiness and one of the including the pledge commodity of is orange. This article aim to wish to know earnings of farmer and margin marketing of orange in Sub-Province of Karo . Result of analysis of farming show the existence of advantage in this commodity conducting, this matter isn't it from ratio of R/C to 2, 97. Acquirement of marketing margin between institutes of marketing in concerned tend to vary and lame. Acquirement of the marketing margin at modern market, retailer, interisland merchant, and merchant of mains market each of Rp 4.300 / kg, Rp 900 / kg, Rp 350 /kg, and Rp 1.000 /kg. Whereas acquirement of marketing margin at merchant of compiler of and countryside of perkoper equal to Rp 150 / kg and of Rp 125 /kg. Mount share farmer of orange to institute of marketing of modern market, retailer, merchant of mains market and interisland merchant each of 10%, 17, 14%, 24,0%, and 28,57%. While to institute of marketing of merchant of compiler of and countryside of perkoper equal to 80% and 72,73%. Economical, orange still profit. This advantage still improved potential corrected the production system of so that the productivity of can be improved. To be expected by this production process can improve quality and amount especially higher level super ordinate again so that have opportunity to access to market the broaderness, especially export.
Keywords: Farming, Margin, Marketing, and Orange